Use of Liming and Incidence of Diseases in Sugarcane - Cruz, José Manoel Ferreira de Lima; Cruz, Manoela Gomes da; Almeida, Lucilo José Morais de; Silva, Edson de Souza; Neto, Djalma Euzébio Simões; Oliveira, Willams José de; Podestá, Guilherme Silva de; Mielezrski, Fabio (Journal of Agricultural Studies, 2021)
This study aimed to evaluate the incidence of red rot, brown leaf spot, and smut in ten sugarcane genotypes during two consecutive cycles, in the absence and presence of limestone. The experimental design consisted of randomized blocks with four replications, in the presence and absence of liming in the following sugarcane genotypes: G1 (RB002754), G2 (RB021754), G3 (RB041443), G4 (RB863129), G5 (RB93509), G6 (RB951541), G7 (RB962962), G8 (RB992506), G9 (SP79-1011), and G10 (VAT90-212) for genotype x environment interaction. The lowest incidences of red rot were observed in G3 (RB041443), G4 (RB863129), G8 (RB992506), and G9 (SP79-1011) for plant cane, and in G3 (RB041443), G4 (RB863129), G5 (RB93509), G8 (RB992506), and G9 (SP79-1011) for ratoon. All genotypes were susceptible to Colletotrichum falcatum, but limestone reduced its incidence in G3 (RB041443), G6 (RB951541), and G10 (VAT90-212) during the first growth cycle, and in G1 (RB002754), G2 (RB021754), G5 (RB93509), G6 (RB951541), G7 (RB962962), and G10 (VAT90-212) in the ratoon crop. Liming also reduced the incidence of brown leaf spot in G4 (RB863129), G6 (RB951541), and G9 (SP79-1011) in plant cane and G6 (RB951541) and G7 (RB962962) in the ratoon crop. Only the G9 genotype (SP79-1011) showed an incidence of smut. The genotypes had different incidence levels of red rot, brown leaf spot, and smut diseases, which varied in the presence of limestone. Limestone use reduced disease incidence as a function of genotype and cutting cycle.